A comparative pharmacological characteristics of two different amlodipine formulations in healthy subjects - Muhammad Hakimi bin Mohd Rashid (Kulliyyah of Pharmacy, International Islamic University Malaysia, 2014)
Amlodipine, a third generation dihydropyridine calcium antagonist was first made by Pfizer Inc. and patented under the name of Norvasc. After its patent expiry, many generic copies were marketed. Amlodiium is a new formulation of amlodipine developed by IIUM pharmaceutical plant. Generic copies in Malaysia must be proven bioequivalent through in-vivo bioequivalence study. This study was conducted to establish bioequivalence and to compare the pharmacodynamics properties and safety profiles of tablet Amlodiium 10mg and the innovator drug, tablet Norvasc 10mg. This was a randomize, open label, two periods, two sequences, cross-over design study conducted in 18 fasted healthy subjects. The two study periods was separated by 2 weeks washout period. In each study period, subjects were given each of the 2 formulations in random sequences. Supine and standing blood pressure, heart rate, electrocardiogram and blood samples were taken immediately prior to dosing (0h), at 1, 2, 4, 6, 8, 10, 12, 24, 48, 72, 96, 120, and 144h post dosing. Subjects were monitored for any adverse events. Serum amlodipine concentrations were measured by a validated assay method using liquid chromatography coupled to tandem mass spectrometry (LC-MS/MS). The lower limit of quantification (LLOQ) was set at 0.10 ng/mL and the linearity up to 12ng/mL was demonstrated with R2 value more than 0.990. The 90% confidence intervals for the between formulations ratio of the log-transformed maximum plasma concentration (Cmax) and the area under the plasma concentration–time curve until the time of last blood samples (AUCt) and until infinity (AUCinf) were within the acceptance range of 80% to 125%. The differences in time to reach Cmax (Tmax) and half-life (T1/2) between both formulations were not statistically significant. The differences in Pharmacodynamics profiles between both formulations were not statistically significant. In conclusion, the test formulation Amlodiium 10 mg tablet is bioequivalent to the reference formulation Norvasc 10 mg tablet.